Response surface methodology as a tool to study the lipase-catalyzed synthesis of betulinic acid ester - Yasin, Yamin; Basri, Mahiran; Ahmad, Faujan; Salleh, Abu Bakar (Wiley Blackwell, 2008)
BACKGROUND: The synthesis of betulinic acid ester using betulinic acid and oleyl alcohol catalyzed by Novozym 435 (immobilized Candida antarctica lipase) was carried out. Response surface methodology (RSM) based on a five-level, three-variable, central composite rotatable design (CCRD) was employed to evaluate the interactive effects of various parameters. The parameters were reaction time (8–16 h), temperature (20–60 ◦C) and enzyme amount (120–160 mg).